Alexidine versus chlorhexidine for endodontic irrigation with sodium hypochlorite - Jain, Kanav (Eur J Dent, 2018)
OBJECTIVE: The objective of this study was to chemically evaluate precipitate formation on irrigation by different concentrations of chlorhexidine (CHX) and alexidine (ALX) with sodium hypochlorite (NaOCl). MATERIALS AND METHODS: Six test tubes were prepared with 1 ml of 4% NaOCl. One milliliter of 2%, 1%, 0.5%, and 0.25% ALX was added to the first four, and in the last two, 1 ml of 2% CHX and 0.2% CHX was added, respectively. Samples were observed for color changes or precipitates at multiple time intervals. All solutions were then centrifuged at 1000 rpm for 10 min and re-examined for precipitates. This process was repeated twice. Fifty freshly extracted premolars were biomechanically prepared, dried, divided into two groups, and irrigated with 10 ml of 4% NaOCl and 10 ml of 2% ALX (Group 1) and 10 ml of 4% NaOCl and 10 ml of 2% CHX (Group 2). These samples were sectioned and observed for precipitates on the dentinal surfaces by scanning electron microscopy (SEM). RESULTS: The color of the solution of ALX and NaOCl stayed transparent and no precipitate was observed. A color change was noted immediately on mixing CHX and NaOCl which did not change with time. Precipitates were only observed in the solutions of CHX with NaOCl and after centrifuging them. SEM views also showed dense precipitates covering the dentinal surface and occluding the dentinal tubules in Group 2. CONCLUSION: The interaction of ALX and NaOCl does not produce precipitates which together with its better antimicrobial action make ALX a more effective and safer replacement for CHX as an adjunctive endodontic irrigant.